Computer-based remediation in Cape Senior Certificate standard grade mathematics - Elgie, Brian James (Rhodes University, Faculty of Education, Department of Education, 1991)
This dissertation begins by reviewing the difficulties experienced in teaching mathematics to pupiis, weak in mathematics, in the Senior Secondary phase of Cape Education Department schools. The possible use of computer-aided instruction (CAl) in improving the examination performance of such pupils is considered. A suitable CAl software program, viz. the SERGO system, is identified and its operation is described in detail. The researcher investigates, both from a quantitative and a qualitative aspect, the change in mathematics examination performance of a number of weak in mathematics pupils, as a result of receiving an extended period of extra tuition on the SERGO system. It needs to be noted that these pupils are passing candidates in other subjects, and have above average intelligence. They are not slow learners. The researcher identifies three categories of pupils who are weak in mathematics. Different programmes of remediation are recommended for each category. The possible use of the SERGO system as a stand-alone instrument of remediation , for pupils working in pairs, and the possible use by H.G. pupils in combined H.G./S.G. classes are also investigated.
Keywords: Mathematics -- Computer-assisted instruction; Mathematics -- Study and teaching -- Audio-visual aids; Mathematics -- Study and teaching -- South Africa